2020
DOI: 10.33448/rsd-v9i1.1608
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem matemática da cinética de secagem de cascas do kino (Cucumis metuliferus)

Abstract: The objective of this work was to perform the chemical and physical characterization of the kino bark (Cucumis metuliferus) as well as to evaluate through mathematical modeling the drying kinetics at different temperatures. The barks were characterized in natura for water content, total and soluble solids, water activity, ashes, pH, total titratable acidity, Ratio and ascorbic acid. The drying kinetics at 60, 70, 80 and 90 °C were determined by adjusting the data to twelve mathematical models using the coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
1
1
0
2
Order By: Relevance
“…It can be noted that the drying air temperature has an influence on the drying rate and the final drying time of the epicarp, because the higher the temperature, the shorter the time for drying the product. This behavior has been reported in studies by several researchers: horned melon peel (Barros et al, 2019), passion fruit peel (Bezerra et al, 2015) and mulungu peel (Martins et al, 2014). The drying times were 21, 15, 13 and 11 hours for temperatures of 40, 50, 60 and 70 °C, respectively, until reaching the final moisture content of 0.05 (d.b.)…”
Section: Resultssupporting
confidence: 75%
“…It can be noted that the drying air temperature has an influence on the drying rate and the final drying time of the epicarp, because the higher the temperature, the shorter the time for drying the product. This behavior has been reported in studies by several researchers: horned melon peel (Barros et al, 2019), passion fruit peel (Bezerra et al, 2015) and mulungu peel (Martins et al, 2014). The drying times were 21, 15, 13 and 11 hours for temperatures of 40, 50, 60 and 70 °C, respectively, until reaching the final moisture content of 0.05 (d.b.)…”
Section: Resultssupporting
confidence: 75%
“…Silva, e Silva, Gama, and Gomes (2014) in their study on thin‐layer drying to determine the drying rate of whole bananas also found Page and Silva et alii as the best models for fitting to the experimental data. In a study conducted with Cucumis metuliferus peels, adjusting mathematical models to the experimental data of drying kinetics, the Page model showed satisfactory fit (Barros et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Entretanto, o modelo de Research, Society and Development, v. 9, n. 9, e405997334, 2020 (CC BY 4.0 Research, Society and Development, v. 9, n. 9, e405997334, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7334 apresentaram ajustes satisfatórios. Santos et al (2020) Research, Society and Development, v. 9, n. 9, e405997334, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7334 Na Tabela 3, encontram-se os valores dos resultados das análises físicas e químicas dos resíduos in natura e das farinhas obtidas. Para os resíduos in natura, foi percebido um elevado teor de água nas amostras, chegando a 86,33 %, onde essa alta concentração pode ser confirmada com os resultados da atividade de água, que alcançou o valor de 0,99.…”
Section: Resultsunclassified